PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NOMOR 45 PADA BAITUL MAL PROVINSI NANGGROE ACEH DARUSSALAM - Ridwan Ibrahim; Tri Handayani (Jurnal Telaah dan Riset Akuntansi, 2009)
This study aimed to answer the question whether the financial statements of the Baitul Mal Aceh have been prepared in accordance with the provinsions of SFAS No.45. Location of the study was conducted at the Baitul Mal Province of Nanggroe Aceh Darussalam. Classified research data in the form of secondary data. This research using qualitative methods to analyze the data, that is by comparing the result with existing theories.The results showed that in general the Baitul Mal has adaopted SFAS No.45. The financial statements at the Baitul Mal has adopted SFAS No. 45 which consists of the consolidated financial position, statement of activities, cash flow statement and notes to financial statements. Consolidated financial position at the Baitul Mal NAD is only made for internal party treasurer in particular, this report has not been published because there is no agreement-making. Report on the activities of the Baitul Mal called the report the calculation and distribution of zakat which describes about the sources of revenue and spending zakat. Presentation of the preparation of their respective financial statements at the Baitul Mal has not yet been fully follow SFAS No. 45, there is material that has not been presented in each report.    Key word : Baitul Mal, Financial Statements